Percepções e ações docentes frente às dificuldades de aprendizagem de estudantes na educação profissional e tecnológica - Neves, Daniela Tatsch (2022)
Learning difficulties are present at all levels of education, however the way in which teachers work with these students is still not often addressed in academic research in Vocational and Technological Education (VTE). Thus, this study aimed to investigate the pedagogical practices of teachers in Vocational and Technological Education (VTE) in relation to students who have learning difficul-ties. This research has a qualitative approach developed through individual semi-structured interviews with teachers in the area of professional and technological education of Colégio Politécnico and Colégio Técnico Industrial of the federal education network in the city of Santa Maria in Rio Grande do Sul - Brazil. As a result, it was found that teachers need continuing education, provided and en-couraged by educational institutions to improve their practice in front of students with learning difficulties. The interviewed professors, in general, make adapta-tions in their plans, but this is not unanimous. The pedagogical practices of teach-ers in professional and technological education in relation to students who have learning difficulties are flexible, with the help of interns who make up the peda-gogical support service. In general, there is no elaboration of a plan adapted for these students. We hope that this research will contribute, especially, to the lives of students enrolled in the VTE who have learning difficulties and to the pedagog-ical practice of their teachers.